2009
DOI: 10.1177/112067210901900521
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Infliximab in Experimental Endotoxin-Induced Uveitis

Abstract: The results provide evidence that intravitreal injection of infliximab suppresses ocular inflammation in a rabbit model of severe endotoxin-induced uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
15
1
1
Order By: Relevance
“…Em outro estudo (26) , doses crescentes de injeções intravítreas de infliximabe mostrou, após 45 dias, alterações nas células de retina com doses superiores a 5 mg. Concluiu-se que 2 mg é uma dose segura para a retina de coelhos. Estudos realizados em coelhos, com a indução de uveíte com uso de endotoxina da salmonela (27) demonstraram que o uso de infliximabe intravítreo, além de não provocar toxicidade, suprimia a inflamação provocada pela endotoxina.…”
Section: Discussionunclassified
“…Em outro estudo (26) , doses crescentes de injeções intravítreas de infliximabe mostrou, após 45 dias, alterações nas células de retina com doses superiores a 5 mg. Concluiu-se que 2 mg é uma dose segura para a retina de coelhos. Estudos realizados em coelhos, com a indução de uveíte com uso de endotoxina da salmonela (27) demonstraram que o uso de infliximabe intravítreo, além de não provocar toxicidade, suprimia a inflamação provocada pela endotoxina.…”
Section: Discussionunclassified
“…In a study on seven groups with four rabbits per group, an intravitreal dose of 2 mg/0.1 mL infliximab was shown to be safe, and this dose was used in our study for the intravitreal injection [9]. In another study on 33 rabbits, an experimental uveitis model was induced, and the efficacy of infliximab at an intravitreal dose of 1 mg/0.1 mL was demonstrated [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IV infliximab reduced the inflammation in an experimental model of uveitis. 9 However, it is still unclear as to which treatment route (systemic vs. IV) is more effective and rapid for ocular inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no histopathologic difference between the IV infliximab (group 3) and the control group. Nevertheless, Hosseini et al 9 showed that histopathological inflammation was reduced effectively on the seventh post-IV infliximab (1 mg/0.1 cc) injection day.…”
mentioning
confidence: 97%
See 1 more Smart Citation